The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1002/mas.10046
|View full text |Cite
|
Sign up to set email alerts
|

Tandem mass spectrometry in the study of fatty acids, bile acids, and steroids

Abstract: Over the last 50 years, the mass spectrometry of lipids has evolved to become one of the most mature techniques in biomolecule analysis. Many volatile and non-polar lipids are directly amenable to analysis by gas-chromatography-mass spectrometry (GC-MS), a technique that combines the unsurpassed separation properties of gas-chromatography with the sensitivity and selectivity of electron ionization mass spectrometry. Less volatile and/or thermally labile lipids can be analyzed by GC-MS, following appropriate sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
203
1
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 266 publications
(217 citation statements)
references
References 185 publications
10
203
1
3
Order By: Relevance
“…There is general agreement as to the structure of the b 1 -12 and b 2 type ions, but some debate as to the structure of the b 2 -CH 2 type ions [53]. The use of deuterium labeled steroids in this current study provide further evidence for the b 1 -12 type ions to consist of the steroid A-ring plus C-19 but minus C-5; and the b 2 type ions to consist of the A ring, C-6 and C-19 (Scheme 3).…”
Section: Fragmentation Of 3-oxo-⌬ 4 Steroids and Their Cationic Derivmentioning
confidence: 99%
See 1 more Smart Citation
“…There is general agreement as to the structure of the b 1 -12 and b 2 type ions, but some debate as to the structure of the b 2 -CH 2 type ions [53]. The use of deuterium labeled steroids in this current study provide further evidence for the b 1 -12 type ions to consist of the steroid A-ring plus C-19 but minus C-5; and the b 2 type ions to consist of the A ring, C-6 and C-19 (Scheme 3).…”
Section: Fragmentation Of 3-oxo-⌬ 4 Steroids and Their Cationic Derivmentioning
confidence: 99%
“…Traditionally, oxysterols are analyzed by GC-MS after derivatization of the hydroxyl groups to trimethylsilyl ethers [31,32]; alternatively cholesterol-like molecules can be analyzed by ES-MS and ES-MS/MS after one of a number of different derivatization reactions [53]. In the current study, molecules with a C 5 -3␤-ol structure have been oxidized to 3-oxo-⌬ 4 steroids and then derivatized to GP hydrazones.…”
Section: Sensitivity Of Analysismentioning
confidence: 99%
“…They also developed an analytical method and conducted stereochemistry studies of all the HDHAs produced by human platelets and rat brain homogenates using chiral LC-thermospray-MS and GC/MS (electron-impact ionization) [11]. Low-energy ionization primarily generates molecular (or pseudo-molecular) ions for collision-induced dissociation (CID) MS/MS analysis, through which the MS/MS spectra obtained are used widely to identify and elucidate the structures of lipid mediators derived from polyunsaturated fatty acids [12][13][14][15][16][17][18][19][20]. The lowenergy CID of eicosanoids includes charge-remote and charge-directed fragmentations [12,21], many of which occur through "␣-hydroxy-␤-ene like rearrangement" as referred to by Murphy, i.e., ␣-cleavage of the carbonOcarbon bond (␣ position to hydroxy group), facilitated by a double bond (ene) in the ␤ position [22].…”
mentioning
confidence: 99%
“…This is due to ESI ions being generated with lower internal energies. However, most published studies utilizing MS/MS for phospholipid analysis were done using FAB because this ionization technique was interfaced with mass spectrometers earlier (Griffiths, 2003). It has also been found that the fragments that are formed vary depending on the mass analyzer.…”
Section: Analysis Of Phospholipidsmentioning
confidence: 99%
“…CID will also create characteristic fragment ions. PC will form ions at M-15, M-60 and M-86 owing to the fragmentation of the choline head group (Griffiths, 2003). PS has an M-87 ion in the negative mode, corresponding to serine loss.…”
Section: Analysis Of Phospholipidsmentioning
confidence: 99%